New heinemann maths, 6, extension textbook - Blair, John T. (Heinemann Harlow, 2002)
"New Heinemann Maths" offers interactive, whole-class teaching, with structured development of mental calculation within the Framework. It covers planning and teaching; pupil material; structure and progression; support for more able children; and easy-to-manage assessment.